Pengaruh bentuk dan orientasi bangunan terhadap penggunaan energi pada tapak berkontur di iklim tropis menggunakan sefaira - Priyanka G. A. S. K. W. Notodipuro; Ariani Mandala (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
One of the biggest contributors to energy usage are built infrastructures (up to 40%). Minimizing energy usage efficiently could reduce cost and give a better impact on the environment in terms of sustainability. As a tropical country that experiences sun exposure throughout the year, designing a building in Indonesia needs to respond to the impact of solar radiation inside the room for comfort and energy-saving effort. In addition, the topography of the site is considered throughout the process of designing a building, in which the site is located on sloped terrain (with a slant of 15 degrees celsius) and may influence the orientation and shape as it affects access to sunlight and view. This paper aims to identify which building orientation and shape of a project have the least energy usage during its preliminary phase on sloped terrains in tropical climate areas. 3 different building orientations (west-east, combination, North-east – South-west) and shapes are analyzed through experimental method by utilizing Sefaira as a plugin to Sketchup software using ASHRAE 90.1 - 2019 (ZONE 2) as material standard for the analysis. This research focuses on how a sloped site, as well as climate, affects building efficiency and how the orientation and shape of the building affect the building’s energy consumption. Difference in characteristics of the land, preferably regarding flat or sloped terrain lands, does not guarantee whether the energy usage will change, but it shows that sloped terrain sites could benefit on reducing the cooling load of a building as well as daylighting.